Eclipse for Dummies - Burd, Barry (Wiley Publishing, 2011)
In his friendly, easy-to-understand style, the bestselling author of Java 2 * For Dummies shows developers how to get up to speed fast on this popular Java IDE * Eclipse, an open source product originally developed by IBM, has an estimated 500,000 users-a 45 percent market share among Java IDEs * Shows Java developers how to maximize programming productivity with Eclipse, covering all the basics as well as advanced techniques such as using Ant, developing new Eclipse plug-ins, and working with Javadocs JAR files